An integrated platform for small-animal hyperthermia investigations under ultra-high-field MRI guidance. (19th May 2018) - Curto, Sergio; Faridi, Pegah; Shrestha, Tej B.; Pyle, Marla; Maurmann, Leila; Troyer, Deryl; Bossmann, Stefan H.; Prakash, Punit
Abstract: Purpose: Integrating small-animal experimental hyperthermia instrumentation with magnetic resonance imaging (MRI) affords real-time monitoring of spatial temperature profiles. This study reports on the development and preliminary in vivo characterisation of a 2.45 GHz microwave hyperthermia system for pre-clinical small animal investigations, integrated within a 14 T ultra-high-field MRI scanner. Materials and methods: The presented system incorporates a 3.5 mm (OD) directional microwave hyperthermia antenna, positioned adjacent to the small-animal target, radiating microwave energy for localised heating of subcutaneous tumours. The applicator is integrated within the 30 mm bore of the MRI system. 3D electromagnetic and biothermal simulations were implemented to characterise hyperthermia profiles from the directional microwave antenna. Experiments in tissue mimicking phantoms were performed to assess hyperthermia profiles and validate MR thermometry against fibre-optic temperature measurements. The feasibility of delivering in vivo hyperthermia exposures to subcutaneous 4T1 tumours in experimental mice under simultaneous MR thermometry guidance was assessed. Results: Simulations and experiments in tissue mimicking phantoms demonstrated the feasibility of heating 21–982 mm 3 targets with 8–12 W input power. Minimal susceptibility and electrical artefacts introduced by the hyperthermia applicator were observed on MR imaging. MR thermometry was in excellent agreement with fibre-optic temperatures measurements (max. discrepancy ≤0.6 °C). Heating experiments with the reported system demonstrated the feasibility of heating subcutaneous tumours in vivo with simultaneous MR thermometry. Conclusions: A platform for small-animal hyperthermia investigations under ultra-high-field MR thermometry was developed and applied to heating subcutaneous tumours in vivo .